SALMON: solvent accessibility, ligand binding, and mapping of ligand orientation by NMR spectroscopy. - Ludwig, C; Michiels, P; Wu, X; Kavanagh, K; Pilka, E; Jansson, A; Oppermann, U; Günther, U (2008)
Quinone oxidoreductase 2 (NQO2) binds the prodrug tretazicar (also known as CB1954, 5-(aziridin-1-yl)-2,4-dinitrobenzamide), which exhibits a profound antitumor effect in human cancers when administered together with caricotamide. X-ray structure determination allowed for two possible orientations of the ligand. Here we describe a new NMR method, SALMON (solvent accessibility, ligand binding, and mapping of ligand orientation by NMR spectroscopy), based on waterLOGSY to determine the orientation of a ligand bound to a protein by mapping its solvent accessibility, which was used to unambiguously determine the orientation of CB1954 in NQO2.